Cell Surface Translocation of Annexin A2 Facilitates Glutamate-induced Extracellular Proteolysis - Valapala, Mallika (American Society for Biochemistry and Molecular Biology, 2014)
Glutamate-induced elevation in intracellular Ca(2+) has been implicated in excitotoxic cell death. Neurons respond to increased glutamate levels by activating an extracellular proteolytic cascade involving the components of the plasmin-plasminogen system. AnxA2 is a Ca(2+)-dependent phospholipid binding protein and serves as an extracellular proteolytic center by recruiting the tissue plasminogen activator and plasminogen and mediating the localized generation of plasmin. Ratiometric Ca(2+) imaging and time-lapse confocal microscopy demonstrated glutamate-induced Ca(2+) influx. We showed that glutamate translocated both endogenous and AnxA2-GFP to the cell surface in a process dependent on the activity of the NMDA receptor. Glutamate-induced translocation of AnxA2 is dependent on the phosphorylation of tyrosine 23 at the N terminus, and mutation of tyrosine 23 to a non-phosphomimetic variant inhibits the translocation process. The cell surface-translocated AnxA2 forms an active plasmin-generating complex, and this activity can be neutralized by a hexapeptide directed against the N terminus. These results suggest an involvement of AnxA2 in potentiating glutamate-induced cell death processes.